Variations in mid-latitude North Atlantic surface water properties during the mid-Brunhes (MIS 9-14) and their implications for the thermohaline circulation - Voelker, Antje (2020)
Stable isotope and ice-rafted debris records from three core sites in the mid-latitude North Atlantic (IODP Site U1313, MD01-2446, MD03-2699) are combined with records of ODP Sites 1056/1058 and 980 to reconstruct hydrographic conditions during the middle Pleistocene spanning Marine Isotope Stages (MIS) 9-14 (300-540 ka). Core MD03-2699 is the first high-resolution mid-Brunhes record from the North Atlantic's eastern boundary upwelling system covering the complete MIS 11c interval and MIS 13. The array of sites reflect western and eastern basin boundary current as well as north to south transect sampling of subpolar and transitional water masses and allow the reconstruction of transport pathways in the upper limb of the North Atlantic's circulation. Hydrographic conditions in the surface and deep ocean during peak interglacial MIS 9 and 11 were similar among all the sites with relative stable conditions and confirm prolonged warmth during MIS 11c also for the mid-latitudes. Sea surface temperature (SST) reconstructions further reveal that in the mid-latitude North Atlantic MIS 11c is associated with two plateaus, the younger one of which is slightly warmer. Enhanced subsurface northward heat transport in the eastern boundary current system, especially during early MIS 11c, is denoted by the presence of tropical planktic foraminifer species and raises the question how strongly it impacted the Portuguese upwelling system. Deep water ventilation at the onset of MIS 11c significantly preceded surface water ventilation. Although MIS 13 was generally colder and more variable than the younger interglacials the surface water circulation scheme was the same. The greatest differences between the sites existed during the glacial inceptions and glacials. Then a north - south trending hydrographic front separated the nearshore and offshore waters off Portugal. While offshore waters originated from the North Atlantic Current as indicated by the similarities between the records of IODP Site U1313, ODP Site 980 and MD01-2446, nearshore waters as recorded in core MD03-2699 derived from the Azores Current and thus the subtropical gyre. Except for MIS 12, Azores Current influence seems to be related to eastern boundary system dynamics and not to changes in the Atlantic overturning circulation.